Adhesion and invasion attributes of Burkholderia pseudomallei are dependent on airway surface liquid and glucose concentrations in lung epithelial cells - Mariappan, Vanitha; Thimma, Jaikumar; Vellasamy, Kumutha Malar; Shankar, Esaki Muthu; Vadivelu, Jamuna (Wiley, 2018)
Physiological constituents in airway surface liquids (ASL) appear to impact the adherence and invasion potentials of Burkholderia pseudomallei contributing to recrudescent melioidosis. Here, we investigated the factors present in ASL that is likely to influence bacterial adhesion and invasion leading to improved understanding of bacterial pathogenesis. Six B. pseudomallei clinical isolates from different origins were used to investigate the ability of the bacteria to adhere and invade A549 human lung epithelial cells using a system that mimics the physiological ASL with different pH, NaCl, KCl, CaCl 2 and glucose concentrations. These parameters resulted in markedly differential adherence and invasion abilities of B. pseudomallei to the lung epithelial cells. The concentration of 20 mM glucose dramatically increased adherence and invasion by increasing the rate of pili formation in depiliated bacteria. Glucose significantly increased adherence and invasion of B. pseudomallei to A549 cells, and presence of NaCl, KCl and CaCl 2 markedly ablated the effect despite the presence of glucose. Our data established a link between glucose, enhanced adhesion and invasion potentials of B. pseudomallei, hinting increased susceptibility of individuals with diabetes mellitus to clinical melioidosis.